FUNDAMENTALS OF ECOLOGY TEACHING METHODOLOGY - Eshtukhtarova Orzigul Shonazarovna (Web of Journals Publishing, 2025)
In the contemporary world, environmental issues have reached a critical level, influencing nearly every aspect of human life, including science, production, politics, economics, urban development, healthcare, and education. Environmental education serves not only as a means of knowledge transmission but as a strategic tool for cultivating ecological consciousness and sustainable behavior. This article explores the theoretical foundations and methodological approaches of teaching ecology, emphasizing the integration of ecological, pedagogical, and psychological perspectives to improve students' environmental literacy and competencies.
Keywords: Environmental education, ecological consciousness, sustainable development, pedagogy, environmental psychology.